Peningkatan Hasil Belajar Siswa Kelas IV Sekolah Dasar Melalui Pembelajaran kontekstual Di SD Negeri Samata Di Kabupaten Gowa - B, muhammad jafar (Universitas Negeri Makassar, 2018)
Abstract. This study was conducted aiming to determine the effectiveness of the implementation of contextual learning in an effort to improve learning outcomes in fourth grade students of SD Negeri Samata, Gowa Regency. The subjects in this study were fourth grade students of Samata State Elementary School, Gowa Regency, academic year 2017/2018. The determination of this class is carried out by researchers based on the results of an investigation of the class taught by the researcher. Researchers predict that this class will occur less contextual problems in learning. Researchers predict that there will be an increase in learning outcomes if done with contextual learning methods through discussions, observations, and presentations. This research approach uses qualitative and quantitative descriptive approaches. Descriptively the data obtained in the form of observations of student activities and teacher activities during the learning process using a contextual approach. The data was analyzed quantitatively. Based on the results of research and data analysis conducted showed that through contextual learning has improved the ability of students in carrying out problem-solving discussions about learning materials in fourth grade elementary school. Through contextual learning about learning material in fourth grade elementary school, there was an increase in the ability of students to present reports on their observations about the activities of both the school environment and the community. The implementation of contextual learning has resulted in students being better able to construct themselves based on their concepts and experiences in the field. Contextual learning in leasamrning material in fourth grade elementary school is a fun learning for students. Students have tried to construct their own knowledge. Learning has formed students to be more active, creative, innovative, independent and collaborative